Guest

2cos(a+b)cos(a-b)=1 so prove that tan^2=1-tan^2(b)/1+3tan^2(b)

2cos(a+b)cos(a-b)=1 so prove that tan^2=1-tan^2(b)/1+3tan^2(b)

Grade:11

2 Answers

Nishant Vora IIT Patna
askIITians Faculty 2467 Points
5 years ago
223-753_Capture.PNG
imran
19 Points
5 years ago
HI,
PLZ GIVE THE FULL SOLUTION FOR THIS QUESTION AFTER WARDS WHAT WE HAVE TO DO

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free